Children’s rough and tumble play: Perspectives of teachers in northern Canadian Indigenous communities. - Stagg Peterson, Shelley; Madsen, Audrey; San Miguel, Jayson; Jang, Soon Young (Early Years, 2016)
This is an Accepted Manuscript of an article published by Taylor & Francis in Early Years: An International Research Journal on September 3 2016, available online: http://www.tandfonline.com/doi/full/10.1080/09575146.2016.1219844. Ten teachers in kindergarten and grade one classrooms in remote northern Canadian Ojibway communities, and two consultants from a First Nations Student Success Program participated in focus group discussions about the place of rough and tumble and superhero play, and teachers’ roles in preventing relational and physically aggressive play in school. This paper reports on issues related to sociocultural influences on perceptions of play involving objects to which Indigenous children assign implicit roles as guns, and teachers’ concerns about external perceptions of teachers’ roles vis-à-vis playful aggression in school. Implications for teacher practice and for teacher education include establishing boundaries and negotiating rules and consequences with students, and teaching problem-solving approaches, particularly in response to relationally aggressive play. Teachers’ expressed need for exposure to research on playful aggression in teacher education and professional development initiatives is consistent with the findings of previous research. This study provides perspectives from teachers in a non—mainstream teaching context on a controversial topic with mixed views coming from researchers and media reports. This work was supported by the Social Sciences and Humanities Research Council of Canada.